Gender differences in solving multiplication and division problems among primary school pupils in the context of Problem-Based Learning (PBL) - Ong, Gaik Suan; Syarifah Kamariah, Wan Mohammad; Wong, Tze Jin; Koo, Lee Feng (Community Practitioners And Health Visitors Association, 2023)
The gender gap in mathematics requires immediate attention as it affects the gender balance in participation in Science, Technology, Engineering and Mathematics (STEM) education, which is recognized as a key enabler of 21st century skills in Malaysia's transition to Industrial Revolution 4.0 (IR 4.0). Therefore, this study was conducted to investigate the difference between genders in solving mathematics problems in primary school using Problem-Based Learning (PBL) technique. A quasi- experimental design was adopted for this study. A total of 27 students (15 girls and 12 boys) from grade 3 primary school were selected to participate in this study. Three hypotheses were put forward in this study. The results show that boys and girls have no significant difference in their performance in solving multiplication and division tasks using PBL. However, the results show that their mathematical performance improved by using the PBL method.